An Overview of the Radiology Features for Medulloblastoma: A Pictorial Review (Department of Radiology, Medical Faculty, University of Brawijaya, 2025)
Among brain cancers, medulloblastoma is the most prevalent in the adolescent population. It is a complex and heterogeneous disease, presenting significant challenges in diagnosis, treatment, and management. This manuscript will explore the current understanding of radiologic follow-up for pediatric patients with medulloblastoma, highlighting recent advances in imaging techniques and their correlation with molecular subgroups. It will also discuss ongoing efforts to personalize therapy based on molecular and skeletal characteristics, aiming to improve survival rates and reduce long-term sequelae in patients with the disease.